The use of tranexamic acid for the treatment of melasma (Research, Society and Development, 2022)
Introduction: The demand related to dermatological care has been increasing in recent years. Growth caused by various dysfunctions that can compromise skin health. Melasma is a chronic hyperpigmentation of the skin, caused by a dysregulation in melanocytes that leads to a localized accumulation of melanin. Tranexamic acid (TA) is part of the first-line treatment. Objective: To describe, based on the literature, the use of tranexamic acid and its effectiveness in the treatment of melasma. Method: For the development of this work, data from the last five years were used, researched in Pubmed, Google Scholar, LILACS and Scielo databases. Result: The articles showed significant improvements in the effect caused by melasma in all administration routes presented, offering safety and minimal side effects, and may highlight TA as an alternative treatment. Conclusion: The data demonstrate the effectiveness of tranexamic acid, which promotes the reduction of epidermal pigmentation, bringing benefits and improving the emotional conditions of patients with melasma.